Physical fitness profile and match analysis of elite junior badminton players: case studies - Kui, W. S. W.; Ler, H. Y.; Woo, M. T. (Innovation and Technology in Sports: Proceedings of the International Conference on Innovation and Technology in Sports, (ICITS) 2022, Malaysia, 2023)
The purpose of this study was to determine the physical fitness profile, heart rate responses, technical and timing analysis of elite junior badminton players. Four elite junior badminton players (2 males & 2 females; Average age = 17.5 years) with a minimum of 12 h of training per week were included in this study. The players completed a series of fitness testing (cardiorespiratory fitness, speed, agility, upper strength & lower strength, and power) to obtain their physical fitness profile. Heart rate responses were recorded during the matches. Videos of both genders were analyzed using a customized badminton tagging panel with video analysis software. Results showed the fitness levels of male players were better than female players. During the matches, female players demonstrated a greater average % HR compared to male players. Match analysis demonstrated that male single favourite shots were net (31.68%) and smash (20.04%), while female favourite shots were clear (25.43%) and drop (19.58%). The winning shots for the males were mostly from smash, while the females` winning shots were from drop. The results of the study provide an insight to the coaches to develop effective training plans for junior players based on gender. (197 words).